Emerging Trends in Science, Engineering and Technology Proceedings of International Conference, INCOSET 2012 - Sathiyamoorthy, S.; Caroline, B. Elizabeth; Jayanthi, J Gnana; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2012)
The present book is based on the research papers presented in the International Conference on Emerging Trends in Science, Engineering and Technology 2012, held at Tiruchirapalli, India. The papers presented bridges the gap between science, engineering and technology. This book covers a variety of topics, including mechanical, production, aeronautical, material science, energy, civil and environmental energy, scientific management, etc. The prime objective of the book is to fully integrate the scientific contributions from academicians, industrialists and research scholars.
Preface -- Acknowledgement -- Table of Contents -- About the editors -- About INCOSET 2012: Conference Details; Organizing Committee; Advisory Board; List of Reviewers -- Papers -- Author Index.
Keywords: Engineering; Geography; Mechanical engineering; Civil engineering; Engineering; Mechanical Engineering; Civil Engineering; Earth Sciences, general